Stability Analysis of a Stochastic Viral Infection Model with General Infection Rate and General Perturbation Terms - Mahrouf, Marouane; Hattaf, Khalid; Yousfi, Noura (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we propose a stochastic viral infection model with general incidence rate. In the proposed model, the stochastic perturbations are modeled by general functions. Further, the global existence and positivity of solutions are investigated. In addition, the stochastic stability of the model is established by using the direct Lyapunov method. Finally, an application of the hepatitis B virus (HBV) is given to validate our theoretical results.